Theoretical research and application development of self-sensing micro-flow injection device. Issue 5 (January 2021) - Huang, Jie; Shi, Liping
Abstract: In this study, the main content is based on theory and application of piezoelectric ceramic digital micro-injection, analyzing the first inverse piezoelectric effect and secondary positive piezoelectric effect of piezoelectric ceramics through theory and experiments, and using its principle to design self-sensing digital micro-injection structure. This paper designs a kind of digital micro-injection device which is based on the first inverse and secondary positive piezoelectric effect by according to the theoretical research and experimental verification of piezoelectric ceramic's piezoelectric effect. Push the syringe plunger under the action of the piezoelectric ceramic's first reverse piezoelectric effect to achieve a fluid flowing. At the same time, secondary piezoelectric effect can sense the injection volume to achieve self-sensing microinjection. Designing the overall structure of the program and validate the feasibility of the program is reasonable and practicable through feasibility experiments.